Alcohol and lactation: A systematic review - Giglia, Roslyn; Binns, Colin (Union Offset Printers, 2006)
The aim of the present paper is to critically review the current literature on the effect of alcohol intake during lactation on the hormonal control of lactogenesis; breast milk and infant blood alcohol concentration; and on the breastfeeding infant. The databases PubMed, CINAHL, Proquest Health and Medical Complete, ScienceDirect and ISI Web of Knowledge were searched for articles published between 1990 and 2005. We found limited research investigating the effect of alcohol intake on the infants of lactating women, with most being conducted using animal models. Results consistently show a decrease in lactational performance in both animal and human studies of alcohol intake and breastfeeding. Alcohol intake by lactating mothers in amounts recommended as ‘safe’ for non-lactating women may have a negative effect on infant development and behaviour. Clear guidelines for alcohol consumption are required for lactating women and health professionals to guide breastfeeding mothers to make educated choices regarding alcohol intake during this critical period of infant development.